The Effect of Culture-Based Culinary Tourism on Tourist Experience and Tourist Advocacy - Widodo, Teguh; Octaviany, Vany (International Journal of Engineering and Technology, 2026)
In tourism literature, there have been many studies investigating the role of local culture in culinary product and its impact on tourist experience. However, there is a lack of studies investigating the role of local culture in other factors of marketing mix. By extending the gastronomy tourism concept, this study proposes a novel concept, namely Culture-Based Culinary Tourism (CBCT) – a concept that augments the role of local culture in the place, people, and physical evidence of culinary product. This study is aimed at examining a conceptual model of the influence of CBCT, which is comprised of Basic Culinary Value and Local Culture Attractiveness, on Tourist Experience and Tourist Advocacy that are intervened by the constructs of Attractiveness of Interaction Venue and Pride in Social Symbol. Data collected from 200 tourists visiting to restaurants in Bandung were processed using the LISREL 8.8 statistical software to test the reliability, validity, and goodness-of-fit index of the model. The results indicate that CBCT has a significant positive impact on Tourist Experience and Tourist Advocacy and the model is fit. Theoretically, this study completes the concept of gastronomy by promoting the novelty of the CBCT model as a key antecedent of Tourist Experience and Tourist Advocacy. For the business, this study recommends the importance of local culture in the effort to boost the marketing mix, which creates a good memorabilia for tourists.